Ensacamento de frutos no cultivo orgânico de tomateiro - Amanda Fialho (2008)
Fruit bagging is an efficient control technique, widely used in theorganic fruit culture. However, there are few results over its efficiency in the tomato organic culture. This work aimed to evaluate the efficiency of tomato bunch bagging of the Santa Clara tomato variety in the control over fruit pests or its effects in the fruit disease incidence, besides verifying the economic viability of this technique in the organic tomato culture. The experiment was conducted in an area with tomato organic culture, in Instituto de Ciências Agrárias da Universidade Federal de Minas Gerais Campus Regional de Montes Claros- (Montes Claros Center for Agriculture of Federal University of Minas Gerais), in the period of September 2007 to January 2008. Bags made with TNT (tissue non tissue), organza tissue, microperfurated plastic and paper were used. The experimental design followed randomized blocks with 5 repetitions. The proportion of lesioned fruit was evaluated for Tuta absoluta (Meiryck) (Lepidoptera: Gelechiidae), Neoleucinodes elegantalis (Guinée) (Lepidoptera: Crambidae), Helicoverpa zea (Boddie) (Lepidoptera:Noctuidae), the incidence of the diseases Erwinia spp. e Alternaria solani on the fruit, the effect of the treatments on the fruit fresh mass and the costs of production together with the economic income generated in each treatment. All the statistical analyses were made through Generalized Linear Models (GLM), following a contrast analysis of 5% probability. The obtained results showed that the bagging use was efficient in the fruit borers' control. The bagged bunches with organza tissue and TNT were the ones which presented the least incidence of the Erwinia spp disease. And concerning the A. solani, bigger control on the protected bunches with TNT was verified. The economic evaluation demonstrated that the bagged bunches with bags produced with TNT provided a bigger economic gain, presenting an average profit of 373,70% bigger than the bunches which were not bagged, making its use viable in the organic tomato culture.